IMPLEMENTATION OF DIGITAL INTERACTIVE MULTIMEDIA DEVELOPMENT BASED ON ARTICULATE STORYLINE - Budiana, Sandi; Rostikawati, Teti; Karmila, Nita; Rahmah, Mursidah; Putri, Layli (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
The research aims to determine the application of developing teaching media by implementing articulatory storylines in learning. Respondents in this study were limited to fourth grade students, the method used was Research and Development by combining the ADDIE model. Feasibility is seen through expert validation, several tests, small group trials, and field trials with indicators of student responses and learning outcomes. The field test was carried out on 40 students. The research results show that digital interactive multimedia and the Articulate Storyline application have great potential for use in learning. Expert validation results obtained an average of 97% with the classification "Very Decent" reinforced by the N-Gain achievement reaching a percentage of 74% in the "High" category, and getting good results with a student response percentage value of 93.1% and response teachers by 94% with the criteria "Very Eligible". Students gave a positive response to interactive multimedia assisted by an articulated and developed storyline application. It can be concluded that digital interactive teaching media is practically used in learning in Theme 9 Subtheme 2 Learning 5 and meets the valid criteria and is very suitable for use in learning in class IV elementary schools.